ESTUDO DE FÁRMACOS ANTICANCERÍGENOS NITROSUREIAS E AVALIAÇÃO IN SITU DE SUAS INTERAÇÕES COM DNA UTILIZANDO BIOSSENSORES ELETROQUÍMICOS DE DNA. - CARVALHO, Paulina Andréa Viana de (2019)
Lomustine (CCNU) and carmustine (BCNU) belong to the class of nitrosureas, which are nnitro compounds capable of alkylate DNA structures. They are lipophilic and can go through the blood-brain barrier, and due to these characteristics, they are used in the treatment of brain tumors and other neoplasms. To understand the interaction mechanisms of these compounds with DNA, voltammetric techniques and DNA-electrochemical biosensors were used. Firstly, the study of the electrochemical behavior of CCNU and BCNU and their degradation in aqueous solution on a glassy carbon electrode (GCE) was performed using voltammetric techniques. From this study, the in situ interaction of both with deoxyribonucleic acid (dsDNA) was investigated in incubated solutions, using dsDNA-electrochemical biosensors and the comet test. Both CCNU and BCNU underwent electrochemical reduction in two irreversible redox processes, diffusion-controlled, pH dependent involving the transfer of two electrons and one proton, each. There was no formation of electroactive reduction products. At pH ≥ 10, the peak potential for the two processes tends to be pH independent by involving only electrons. A reduction mechanism of the CCNU and BCNU in neutral media was proposed. In addition, both antineoplastics underwent spontaneous degradation in aqueous solution over the incubation time, without the formation of electroactive degradation products. The CCNU and BCNU degradation process was more evident in a basic medium. The in situ interaction of CCNU and BCNU with dsDNA showed these pro-drugs interacted with DNA initially causing the condensation of the double helix strands and then the unwinding of these strands. Moreover, free guanine (Gua) was released and oxidative damage caused to dsDNA by both compounds were observed, since 8-oxoguanine (8-oxoGua) and 2,8-dihydroxyadenine (2,8-DHA) were detected. These results were confirmed by the poly (dA)- and poly [dG]-electrochemical biosensors, which demonstrated the oxidative damage caused by dsDNA in both bases, guanine and adenine, by the CCNU degradation product(s). BCNU caused oxidative damage only in the guanine. The comet assay indicated breaks in the single strand of DNA, corroborating with the studies performed by differential pulse voltammetry.